2015
DOI: 10.1007/s10103-015-1822-6
|View full text |Cite
|
Sign up to set email alerts
|

Immediate results of photodynamic therapy for the treatment of halitosis in adolescents: a randomized, controlled, clinical trial

Abstract: Photodynamic Therapy in Adolescents Halitosis ( https://clinicaltrials.gov/ct2/show/NCT02007993?term=NCT02007993&rank=1 )Number: NCT02007993FUNDING:FAPESPNumber: 2013/13032-8.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 34 publications
2
42
1
2
Order By: Relevance
“…Antimicrobial PDT was performed with the THERAPY XT‐EC ® device (DMC ABC Equipamentos Médicos e Odontológicos, São Paulo, Brazil), with red laser emission (660 nm) and a beam spot area of 0.094 cm with in an irradiated area of 0.254 cm 2 per point . A single session of antimicrobial PDT was performed with 0.005% methylene blue (Fórmula e Ação, São Paulo, Brazil) applied to the middle and posterior portions of the tongue for 5 minutes of pre irradiation time.…”
Section: Methodssupporting
confidence: 93%
“…Antimicrobial PDT was performed with the THERAPY XT‐EC ® device (DMC ABC Equipamentos Médicos e Odontológicos, São Paulo, Brazil), with red laser emission (660 nm) and a beam spot area of 0.094 cm with in an irradiated area of 0.254 cm 2 per point . A single session of antimicrobial PDT was performed with 0.005% methylene blue (Fórmula e Ação, São Paulo, Brazil) applied to the middle and posterior portions of the tongue for 5 minutes of pre irradiation time.…”
Section: Methodssupporting
confidence: 93%
“…Also, it has been suggested that the use of antimicrobial agents is associated with some collateral effects, such as unpleasant taste, staining effects and especially harm to normal oral microflora [ 31 ]. In contrast, aPDT has been proven as a good complementary treatment for this condition [ 7 , 20 22 ]. As opposed to conventional antimicrobial methods, aPDT has the advantages of being a non-invasive procedure, it does not result in undesired side effects, and the development of resistance by bacteria is unlikely [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results immediately after the different treatments are the most important ones, as they will really show their efficacy. Additionally, the investigations using aPDT for the treatment of halitosis show its effects immediately after treatment [ 7 , 21 , 22 ]. Furthermore, this trial was designed to be applied in the dental practice in the future, so the 7-day interval also represents a period in which patients could come back to the dental office, retake the halimetry and repeat the aPDT, if necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This reaction results in a phototoxic effect on microbes providing antimicrobial activity to the tissues exposed to PDT. The dorsal tongue is targeted and treated, resulting in an antimicrobial effect on odor causing microbes, thus reducing oral malodor (Costa da Mota et al 2016;Lopes et al 2014Lopes et al , 2016.…”
Section: Diagnostic Toolsmentioning
confidence: 99%